If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (q + -10) * 6 = 48 Reorder the terms: (-10 + q) * 6 = 48 Reorder the terms for easier multiplication: 6(-10 + q) = 48 (-10 * 6 + q * 6) = 48 (-60 + 6q) = 48 Solving -60 + 6q = 48 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 6q = 48 + 60 Combine like terms: -60 + 60 = 0 0 + 6q = 48 + 60 6q = 48 + 60 Combine like terms: 48 + 60 = 108 6q = 108 Divide each side by '6'. q = 18 Simplifying q = 18
| -(x+11)-4=7x+3 | | (e+4)*4=24 | | (x+6)(2x+5)=0 | | 9b-22=-18 | | 188+X=2279 | | 43-(-r)=15 | | 2b-(-2)=16 | | 1-(-2c)=-3 | | 3n-(-4)=19 | | 8x^7-5x^5+15x^4= | | 5x(2x-6)=-20 | | -7=3-2t | | 4s+9=12 | | -2r+-7=-6 | | 2q-8=2 | | 36+72+X=183 | | 3j+8=-10 | | 2j+7=4 | | 1=0t+.5*9.8*t*t | | 4f-12=4 | | 10=4+2m | | 10=4m+2 | | 2s-(-2)=18 | | 9x=x | | 8x-8x+8x-8x+8x=0 | | Vf=Vo+2ax(a) | | 2y+4z+6=0 | | Vf=Vo+2ax | | 29-4x=14-9 | | 2x^2-y^2=2 | | 2x+10=-10-2x | | 3a-2bi=6-8i |